SCHOOL LIVING: CLASSROOM MANAGEMENT IN SCHOOL FUNDAMENTAL AND MIDDLE SCHOOL IN THE STATE OF RS, BRAZIL - de Souza Santana, Gilson (Revista Gênero e Interdisciplinaridade, 2023)
The article addresses indiscipline as one of the primary obstacles for teachers in the classroom. Based on the main reasons for indiscipline, the solutions found in the literature, and the observation of successful conduct, a technique to manage the teacher-student relationship was developed during the 2011 school year in 8th-grade classes. The goal is to give students the autonomy to perceive their natural responsibilities in society, collaborating in constructing a new authority figure in the classroom. The experiment resulted in a clear paradigm shift between a classroom where management was not applied (control group) and the classrooms where the technique was used. More than creating an environment in which the elements that favor teacher stress were attenuated, with an improvement in school performance, the students’ ability to democratically act or react when faced with certain situations, colleagues, and teachers emerged.